Evaluation of pancytopenia on bone marrow aspiration- study at a tertiary care center in Kashmir valley, India - Khan, Subuh Parvez; Geelani, Sajad; Khan, Fiza Parvez; Ali, Noorjahan; Akhter, Shazieya; Shah, Sumayya; Bashir, Nusrat; Rasool, Javid (International Journal of Advances in Medicine, 2018)
Background: Pancytopenia refers to combination of anaemia, leukopenia and thrombocytopenia. It may be a manifestation of a wide variety of disorders, which primarily or secondarily affect the bone marrow. However, aetiology of pancytopenia varies from one geographical region to another. Bone marrow aspiration plays an important role in identifying the cause of pancytopenia. This study was carried to identify the causes of pancytopenia and to find out the bone marrow morphology in cases of pancytopenia. Methods: This study was conducted in the department of haematology in a tertiary care center in Kashmir valley for a period of 3 years. Inclusion criteria: cases with hemoglobin less than 10 gm/dl, total leucocyte count of less than 4000/mm3 and platelet count less than 100,000/mm3 were included in the study. Exclusion criteria: Patients receiving chemotherapy/radiotherapy were excluded from the study. Bone marrow aspiration (BMA) was performed from posterior iliac crest of the patients. Bone marrow aspiration smears were stained with Leishman stain for microscopy. Results: A total of 334 cases were studied during a period of 3 years. Age of patients ranged from 1 year to 85 years with mean of 43.59 years.180 cases were male, and 154 cases were female with male:female ratio of 1.2 :1. The commonest cause of pancytopenia was megaloblastic anemia seen in 103 cases (30.8%) followed by dual deficiency anemia seen in 69 cases (20.7%).37 cases (11%) were of acute leukaemia. Aplastic anemia was seen in 35 cases(10.5%). Other causes of pancytopenia were myelodysplastic syndrome, multiple myeloma, iron deficiency anemia and hypersplenism. Conclusions: Bone marrow aspiration in patients of pancytopenia helps in the identification of the underlying cause in most of the cases. BMA is helpful for understanding the disease process; and in planning further investigations and management of cytopenia patients.